Association between Personality Traits, Schema Modes, and ABO Blood Groups: A Cross-Sectional Study - Nosheen Khalily; Tamkeen Saleem; Wardah Ishfaq, (ASIAN Journal of International Peace & Security (AJIPS), 2025)
This study investigated the relationship between personality traits and schema modes across gender, and ABO blood groups in adults. Using a purposive sampling technique, a total of 108 participants were recruited. Two instruments were used for data collection: the NEO Five-Factor Inventory and the Schema Mode Inventory – Short Version. Data were analyzed using SPSS-24, and results indicated high reliability for both scales (α= 0.73 for the NEO Five-Factor Inventory; Cronbach’s alpha (α= 0.91) for the Schema Mode Inventory). Independent-samples t-tests indicated that females scored significantly higher than males on Extraversion, Openness to Experience, Agreeableness, Conscientiousness, and all schema modes, including Vulnerable Child, Angry Child, Impulsive Child, Compliant Surrender, Demanding Parent, and Healthy Adult. One-way ANOVA revealed significant differences across blood groups for personality traits (neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness). No significant differences were found for any schema modes across blood groups. These findings support robust associations between personality traits and schema modes and highlight gender-related differences in schema activation. However, ABO blood groups did not demonstrate a direct relationship with schema modes, suggesting that biological markers exert limited influence on these schemas.